W-ALGEBRAS FROM HEISENBERG CATEGORIES. (13th July 2016) - Cautis, Sabin; Lauda, Aaron D.; Licata, Anthony M.; Sussan, Joshua
Abstract : The trace (or zeroth Hochschild homology) of Khovanov's Heisenberg category is identified with a quotient of the algebra $W_{1+∞ }$ . This induces an action of $W_{1+∞ }$ on the center of the categorified Fock space representation, which can be identified with the action of $W_{1+∞ }$ on symmetric functions.